Membuat Perencanaan Bisnis Sederhana Dengan Menggunakan Business Model Canvas (BMC) Bagi Siswa SMA Solideo Tangerang - Shierli Wijaya (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The aim of community service activities is to increase students' understanding of managing a business, namely how to prepare a simple Business Plan using the Business Model Canvas (BMC). The BMC method is a very well-known business model and is quite widely used nowadays in the world of business management, especially entrepreneurship. This is because BMC has an overview of the core components of creating a Business Plan more easily through one canvas sheet. The method used in this activity is through lectures and learning discussions in class using Power Point learning media and videos delivered so that students better understand the topic being discussed. Then the students were given the opportunity to ask questions and also directly create a Business Model Canvas by dividing them into 6 groups, each consisting of 8 people. This activity was held on Friday, August 9, 2024, at Pradita University, with a total of 47 students from Solideo-Tangerang High School participating in the activity. From the results of the pre-test in the form of questions given to 25 students, initially their knowledge about the Business Model Canvas was still in the category lack of understanding. Meanwhile, the post-test results show that the students have increased their knowledge with very good understanding.